2016
DOI: 10.1002/cam4.781
|View full text |Cite
|
Sign up to set email alerts
|

Genetic alterations of differentiated thyroid carcinoma in iodine‐rich and iodine‐deficient countries

Abstract: BRAF V600E mutation, RET rearrangements, and RAS mutations are the common genetic alterations in differentiated thyroid carcinomas derived from follicular thyroid cells. However, the relationship between these alterations and iodine intake is still controversial. To clarify the influence of iodine intake on the occurrence of differentiated thyroid carcinomas, we performed molecular analyses for two differentiated carcinomas, papillary thyroid carcinomas (PTCs) and follicular thyroid carcinomas (FTCs), from an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
42
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 41 publications
1
42
1
1
Order By: Relevance
“…The prevalence of the BRAF V600E mutation in PTCs in East Asian countries including Japan is high. The prevalence of the BRAF V600E mutation was reported to be dependent on the amount of iodine intake 29 ; however, very recently it has been demonstrated that there was no difference in the BRAF V600E prevalence between Japan, an iodine-rich country, and Vietnam, an iodine-deficient country 30 . Interestingly, in the meta-analysis by Kim et al .…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of the BRAF V600E mutation in PTCs in East Asian countries including Japan is high. The prevalence of the BRAF V600E mutation was reported to be dependent on the amount of iodine intake 29 ; however, very recently it has been demonstrated that there was no difference in the BRAF V600E prevalence between Japan, an iodine-rich country, and Vietnam, an iodine-deficient country 30 . Interestingly, in the meta-analysis by Kim et al .…”
Section: Discussionmentioning
confidence: 99%
“… 31 In contrast, a very recent study showed no differences in genetic alterations of PTC from iodine-rich (Japan) and iodine-deficient (Vietnam) countries. 32 Thus, there is still no consensus regarding the association of iodine intake and the high prevalence of the BRAF V600E mutation in patients with PTC in iodine sufficient areas. Therefore, these associations should be further elucidated in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the benign nodules, 48 PTC samples and surrounding tissues, which were obtained from pathology archive materials, were also taken into this study. Their histopathological evaluations were performed according to WHO criteria from 2004 [27]. The PTC samples were divided into two groups based on tumor diameter.…”
Section: Patientsmentioning
confidence: 99%